Chloroplastic iron-sulfur scaffold protein NFU3 is essential to overall plant fitness. (1st February 2017) - Nath, Krishna; O'Donnell, James P.; Lu, Yan
ABSTRACT: A previous study showed that Nitrogen-Fixing-subunit-U-type protein NFU3 may act an iron-sulfur scaffold protein in the assembly and transfer of 4Fe-4S and 3Fe-4S clusters in the chloroplast. Examples of 4Fe-4S and 3Fe-4S-requiring proteins and complexes include Photosystem I (PSI), NAD(P)H dehydrogenase, and ferredoxin-dependent glutamine oxoglutarate aminotransferases. In this paper, the authors provided additional evidence for the role of NFU3 in 4Fe-4S and 3Fe-4S cluster assembly and transfer, as well as its role in overall plant fitness. Confocal microscopic analysis of the fluorescently-tagged NFU3 protein confirmed the chloroplast localization of the NFU3 protein. Detailed analysis of chlorophyll fluorescence data revealed that a substantial increase in minimal fluorescence is the primary contributor to the decrease in PSII maximum photochemical efficiency observed in the nfu3 mutants. The substantial increase in minimal fluorescence in the nfu3 mutants is probably the result of an impaired PSI function, blockage of electron flow from PSII to PSI, and over-accumulation of reduced plastoquinone at the acceptor side of PSII. Analyses of seed morphology and germination showed that NFU3 is essential to seed development and germination, in addition to plant growth, development, and flowering. In summary, NFU3 has wide-ranging effects on many biologic processes and is therefore important to overall plant fitness. NFU3 may exert these effects by modulating the availability of 4Fe-4S and 3Fe-4S clusters to 4Fe-4S and 3Fe-4S-requiring proteins and complexes involved in various biologic processes.